Biomarkers in breast cancer - Duffy, Joe (Henry Stewart Talks, 2012)
Biomarkers role in determining prognosis in breast cancer, Therapy prediction, Postoperative surveillance -Monitoring therapy, Estrogen receptor, HER2, uPA/PAI-1, Oncotype DX, CA 15-3